Answer:
[tex]z^{5}[/tex] = - 12 + 316 i
Step-by-step explanation:
Given that -
z = 3 + i
[tex]z^{2}[/tex] = [tex]( 3 + i )^{2}[/tex]
[tex]z^{2}[/tex] = 9 + [tex]i^{2}[/tex] + 6 i
[tex]z^{2}[/tex] = 9 - 1 + 6 i
[tex]z^{2}[/tex] = 8 + 6 i
[tex]z^{3}[/tex] = [tex]z^{2}[/tex] × z
[tex]z^{3}[/tex] = ( 8 + 6 i ) × ( 3 + i )
[tex]z^{3}[/tex] = 24 + 8 i + 18 i + 6 i²
[tex]z^{3}[/tex] = 24 + 26 i - 6
[tex]z^{3}[/tex] = 18 + 26 i
[tex]z^{5}[/tex] = [tex]z^{2}[/tex] × [tex]z^{3}[/tex]
[tex]z^{5}[/tex] = ( 8 + 6 i ) × ( 18 + 26 i )
[tex]z^{5}[/tex] = 144 + 208 i + 108 i + 156 i²
[tex]z^{5}[/tex] = 144 + 316 i -156
[tex]z^{5}[/tex] = - 12 + 316 i